LIPID DISTRIBUTION IN BODY AND SKIN OF FOUR SPECIES OF MARINE FISH. - MATHEW, P T; DEVADASAN, K; VENKATARAMAN, R (Fishery Technology, 2017)
The paper presents results of a study on the analytica characteristics of lipids from the skin and muscle of four important species of Gujarat coast fishes. Changes in characteristics like saponification value, iodine value and unsaponifiable matter of these lipids during different months of the year are also reported.